Magnetic Resonance T2* Is Increased in Patients With Early‐Stage Achilles and Patellar Tendinopathy. Issue 3 (14th March 2021) - Malmgaard‐Clausen, Nikolaj M.; Tran, Peter; Svensson, Rene B.; Hansen, Philip; Nybing, Janus D.; Magnusson, Stig Peter; Kjær, Michael
Abstract : Background: T2 * mapping has proven useful in tendon research and may have the ability to detect subtle changes at an early stage of tendinopathy. Purpose: To investigate the difference in T2 * between patients with early tendinopathy and healthy controls, and to investigate the relationship between T2 * and clinical outcomes, tendon size, and mechanical properties. Study Type: Prospective cross‐sectional. Subjects: Sixty‐five patients with early tendinopathy and 25 healthy controls. Field Strength/Sequence: Three Tesla, ultrashort time to echo magnetic resonance imaging. Assessment: Tendon T2 * was quantified using a monoexponential fitting algorithm. Clinical symptoms were evaluated using the Victorian Institute of Sports Assessment‐Achilles/Patella (VISA‐A/VISA‐P). In vivo mechanical properties were measured using an ultrasound‐based method that determined force and deformation simultaneously in tendons of patellar tendinopathy patients. Statistical Tests: A generalized linear model adjusted for age was applied to investigate the difference between patients and controls. In the two patient groups, linear regressions were applied to investigate the association between T2 * and tendon size, clinical outcomes, and biomechanical properties. Results: There was a significant difference in T2 * between patients and healthy controls (204.8 [95% CI: 44.5–365.0] μsec, P  < 0.05). There was a positive correlation between tendon size and T2 * for both Achilles ( r  = 0.72; P  < 0.05) and patellar tendons ( r  = 0.53; P  < 0.05). There was no significant correlation between VISA‐A and T2 * ( r  = −0.2; P  = 0.17) or VISA‐P and T2 * ( r  = −0.5; P  = 0.0504). Lastly, there was a negative correlation between modulus and T2 * ( r  = −0.51; P  < 0.05). Data Conclusions: T2 * mapping can detect subtle structural changes that translate to altered mechanical properties in early‐phase tendinopathy. However, T2 * did not correlate with clinical scores in patients with early‐phase Achilles and patellar tendinopathy. Thus, T2 * mapping may serve as a tool for early detection of structural changes in tendinopathy but does not necessarily describe the clinical severity of disease. Level of Evidence: 1 Technical Efficacy Stage: 2